Evaluation of Workplace Literacy Programs. A Profile of Effective Instructional Practices - Mikulecky, Larry; Lloyd, Paul; National Center on Adult Literacy, Philadelphia, PA. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1996)
A study of 10 groups of learners in workplace literacy programs at 6 companies was used to develop and refine a data-based model for evaluating workplace literacy programs. The learners (n=181) completed pre- and post-assessments. In a structured one-on-one interview, information was gathered on learners' beliefs about literacy and their own literacy effectiveness. The interviews also focused on literacy practices and learners' plans for 1, 5, and 10 years ahead. To measure job-specific literacy processes and abilities, all site coordinators participated in the development of job-related scenarios based on workplace reading materials. They also provided information about curriculum and classroom practices. An analysis of the aggregated results compared curriculum and classroom practice with the impact of each program and used analysis of variance to determine which program practices lead to success and in what areas. The programs were most effective at improving learners' literacy performance, literacy strategies and processes, and learners' beliefs and plans related to literacy. The analysis of variance allowed development of a data-driven profile of thresholds for effective program practices. This profile suggests that these gains are linked to an environment intense with the use of workplace reading and writing materials, and providing regular discussion and feedback to learners' literacy processes, beliefs about personal literacy effectiveness, and future educational plans. Appendixes include a list of 17 references, list of course characteristics, learner results, and instruments used to gather learner data. (YLB)
Availability: National Center on Adult Literacy, University of Pennsylvania, Publications, 3910 Chestnut Street, Philadelphia, PA 19104-3111 (order no. TR96-03).
Sponsoring Agency: Office of Educational Research and Improvement (ED), Washington, DC.
Contract Number: R117Q00003.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Adult Education; Adult Literacy; Educational Research; Literacy Education; Program Effectiveness; Program Evaluation; Student Attitudes; Workplace Literacy; Reports, Evaluative